2011
DOI: 10.1016/j.plantsci.2011.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes of iron uptake in N2-fixing common bean nodules during iron deficiency

Abstract: Iron is an important nutrient in N(2)-fixing legume nodules. The demand for this micronutrient increases during the symbiosis establishment, where the metal is utilized for the synthesis of various iron-containing proteins in both the plant and the bacteroid. Unfortunately, in spite of its importance, iron is poorly available to plant uptake since its solubility is very low when in its oxidized form Fe(III). In the present study, the effect of iron deficiency on the activity of some proteins involved in Strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 40 publications
3
22
0
1
Order By: Relevance
“…Like in roots, transporters homologues to iron regulated transporter (IRT1) should be present in nodules. The amount of this protein was increased under Fe deficiency also in nodules enabling them to acquire Fe directly from the soil nutrient solution (Slatni et al, 2011). Additionally, Slatni et al (2011) showed that also H + -ATPase activity and protein level were increased under Fe deficiency in nodules of both cultivars, mainly in Flamingo.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Like in roots, transporters homologues to iron regulated transporter (IRT1) should be present in nodules. The amount of this protein was increased under Fe deficiency also in nodules enabling them to acquire Fe directly from the soil nutrient solution (Slatni et al, 2011). Additionally, Slatni et al (2011) showed that also H + -ATPase activity and protein level were increased under Fe deficiency in nodules of both cultivars, mainly in Flamingo.…”
Section: Introductionmentioning
confidence: 94%
“…The amount of this protein was increased under Fe deficiency also in nodules enabling them to acquire Fe directly from the soil nutrient solution (Slatni et al, 2011). Additionally, Slatni et al (2011) showed that also H + -ATPase activity and protein level were increased under Fe deficiency in nodules of both cultivars, mainly in Flamingo. From the data obtained in this previous work we might now hypothesise that, when common bean plants grow with low Fe availability, nodules acquire the capacity to take up Fe not only from the plant cytosol, but also directly from the nutrient solution.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations